2009
DOI: 10.1016/j.apmr.2009.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Fear, Anxiety, and Depression With Physical Function in Patients With Knee Osteoarthritis

Abstract: Objectives To explore whether the psychologic variables anxiety, depression, and fear-avoidance beliefs, and interactions between these variables, are associated with physical function in patients with knee osteoarthritis (OA). We hypothesized lower levels of function would be related to higher anxiety, higher depression, and higher fear-avoidance beliefs, and that high levels of 2 of these factors simultaneously might interact to have a greater adverse effect on physical function. Design Cross-sectional, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(150 citation statements)
references
References 37 publications
4
132
8
Order By: Relevance
“…Many participants found themselves in a negative cycle about fear of wear and tear, and reduced activity. This is commonly reported in the literature surrounding osteoarthritis [23]. In this instance the participants, (none of whom had osteoarthritis) had entered a cycle of fear- Negative belief systems were demonstrated through fear-avoidance, but in some participants catastrophising was also portrayed.…”
Section: Having Spoken With My Physiotherapist I Know It Is Not Actuamentioning
confidence: 52%
“…Many participants found themselves in a negative cycle about fear of wear and tear, and reduced activity. This is commonly reported in the literature surrounding osteoarthritis [23]. In this instance the participants, (none of whom had osteoarthritis) had entered a cycle of fear- Negative belief systems were demonstrated through fear-avoidance, but in some participants catastrophising was also portrayed.…”
Section: Having Spoken With My Physiotherapist I Know It Is Not Actuamentioning
confidence: 52%
“…22 Fear of pain and reinjury was associated with function for patients in the return-to-sports phase of rehabilitation following anterior cruciate ligament reconstruction, 3 and also with self-report of disability in patients with foot and ankle pain. 23 In other studies for lower extremity conditions, fear-avoidance beliefs were associated with selfreport of knee function in patients with knee osteoarthritis 32 and were predictive of pain and function outcomes in patients with patellofemoral pain. 29 Collectively, these studies suggest that the FAM is not specific to low back pain and may have clinical applications for a variety of musculoskeletal pain conditions.…”
Section: T T Resultsmentioning
confidence: 99%
“…Previous studies in physical therapy settings have indicated that the FABQ-W might have better predictive validity for outcomes than the FABQ-PA. 4,8,11 The current study focused on the FABQ-PA because, unlike the FABQ-W, it has been used across different anatomical areas. 5,12,29,32 Our data are, therefore, only applicable to the FABQ-PA, and should not be generalized to studies or clinical environments that used the FABQ-W.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations